The Effect of NPM and EPS Profitability Signals on Stock Return in the Post-Pandemic Pharmaceutical Sector - Faiz Said Bachmid (Review of Accounting and Business, 2026)
Introduction/Main Objectives: This study examines the effect of profitability signals, namely Net Profit Margin (NPM) as a measure of operational efficiency and Earnings per Share (EPS) as an indicator of shareholder value, on stock returns in Indonesia’s pharmaceutical sector during the post-pandemic period (2021–2023). The study aims to identify how investors respond to profitability information under changing market conditions. Background Problems: Previous studies have reported inconsistent findings regarding the effects of NPM and EPS on stock returns. This study investigates whether investors prioritize operational performance or direct financial value signals during a period of industry transition and uncertainty. Novelty: This research extends signaling theory by examining investor behavior during post-pandemic market disruption, reducing cross-industry variation through a homogeneous sector sample, and proposing an empirical framework for investor signal prioritization. Research. Methods: A quantitative ex post facto approach was employed using panel data from seven listed pharmaceutical companies, resulting in 21 firm-year observations selected through purposive sampling. Data were analyzed using a Fixed Effect Model panel regression based on audited financial statements and year-end stock prices. Finding/Results: The results show that EPS has a significant positive effect on stock returns (p < 0.01), while NPM has no significant effect (p > 0.05). Together, both variables significantly influence stock returns with an Adjusted R² of 0.571. ,Conclusion: The findings support signaling theory and indicate that investors prioritize direct value-related indicators over operational efficiency measures.